2015
DOI: 10.1016/j.chembiol.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Selective N-Hydroxyhydantoin Carbamate Inhibitors of Mammalian Serine Hydrolases

Abstract: Serine hydrolase inhibitors, which facilitate enzyme function assignment and are used to treat a range of human disorders, often act by an irreversible mechanism that involves covalent modification of the serine hydrolase catalytic nucleophile. The portion of mammalian serine hydrolases for which selective inhibitors have been developed, however, remains small. Here, we show that N-hydroxyhydantoin (NHH) carbamates are a versatile class of irreversible serine hydrolase inhibitors that can be modified on both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 48 publications
(67 reference statements)
1
81
0
Order By: Relevance
“…Recent studies by our lab and others have found using chemical proteomics that small molecules can accumulate in the lysosome to furnish much greater engagement of proteins than would be predicted based on in vitro experiments (Cognetta et al, 2015, Zuhl et al, 2016). We therefore tested whether lysosomal accumulation may underlie the in situ activity of inhibitor 1 /probe 4 against cathepsins by treating CTSC-transfected cells with the lysosomal neutralizing agents ammonium chloride (NH 4 Cl, 10 mM, 15 min) or bafilomycin A1, a vacuolar H + -ATPase inhibitor (10 nM, 15 min), followed by in situ exposure to probe 4 .…”
Section: Resultsmentioning
confidence: 96%
“…Recent studies by our lab and others have found using chemical proteomics that small molecules can accumulate in the lysosome to furnish much greater engagement of proteins than would be predicted based on in vitro experiments (Cognetta et al, 2015, Zuhl et al, 2016). We therefore tested whether lysosomal accumulation may underlie the in situ activity of inhibitor 1 /probe 4 against cathepsins by treating CTSC-transfected cells with the lysosomal neutralizing agents ammonium chloride (NH 4 Cl, 10 mM, 15 min) or bafilomycin A1, a vacuolar H + -ATPase inhibitor (10 nM, 15 min), followed by in situ exposure to probe 4 .…”
Section: Resultsmentioning
confidence: 96%
“…Highthroughput approaches, including fluorescence polarization-based ABPP (FluoPol-ABPP; Figure 4b) have been designed to overcome this limitation. 62 Recently, competitive ABPP has led to the discovery of new classes of inhibitors including carbamate, [63][64][65] aza-β-lactams, 66 β-lactones, 67 and reversible piperazine amide 68 (serine hydrolase inhibitors), α-ketoheterocyclic compounds 69 (diacylglycerol lipase inhibitors) and many others. 68 This technique was applied in a study by Yang et al 48 in which they assessed the potency and identified off-targets of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 orlistat inhibitor of FASN.…”
Section: Competitive Abppmentioning
confidence: 99%
“…Thus, the study by Cognetta et al (2015) provides new pharmacological tools that target serine hydrolases PPT1 and ABHD4 with good selectivity in vivo. These enzymes had heretofore been difficult to study because of their lack of reactivity toward broad-based fluorophosphonate activity-based probes.…”
mentioning
confidence: 98%
“…In this issue of Chemistry & Biology, Cognetta et al (2015) describe new pharmacological tools, including N-hydroxyhydantoin-containing carbamate inhibitors and an activity-based probe, for palmitoyl protein thioesterase 1 and alpha, beta-hydrolase domain-4 that expand the toolkit for the serine hydrolases.…”
mentioning
confidence: 99%
See 1 more Smart Citation